Sustainable Consumer Behavior and Food Marketing - Meixner, Oliver; Riefler, Petra; Schanes, Karin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In light of the considerable impact of global food supply chains on climate change, more sustainable ways of producing, distributing, and consuming food appear critical for sustainable development. With the aim of contributing to this topic, this Special Issue on sustainable food consumption and food marketing addresses various relevant issues related to food consumption, including innovative and sustainable forms of food production and consumption, animal welfare and meat consumption, price transmission, social media communication, alternative food production, and organic agriculture, among others. As such, this Special Issue sheds light on more sustainable and carbon-friendly food production and consumption systems from various angles. It delivers valuable scientific evidence for the transformation of current carbon-based food supply chains to more eco-friendly, fair, and future-oriented food supply chains.